Pencegahan dan Penyuluhan Penyakit Kecacingan Pada Anak Sekolah Dasar Oehau Kabupaten Kupang Nusa Tenggara Timur - Meliance Bria; Ni Made Susilawati (Jurnal Pengabdian Ilmu Kesehatan, 2023)
Worms are a health problem that is still common. Worms caused by a group of soil-borne intestinal worms known as Soil Transmitted Helminths (STH). This community service is carried out with the aim of carrying out prevention and counseling about environmental health, especially in helminthiasis in elementary school children in Oehau, Kupang District, East Nusa Tenggara Province. This activity conducts counseling and examination of the community on how to deal with helminthiasis in elementary school children with a subject of 41 children at School Oehau. The results showed that out of 41 samples there were 4 samples that were positively infected with the Soil Transmitted Helminths worm species, the Ascaris lumbricoides egg species with a prevalence of 9.8%. Children's behavior by 73%. Children's knowledge of helminthiasis is 87%. Sanitation of the children's home environment by 88%. Therefore, it is suggested to teachers and parents and especially elementary school children to further improve the Clean and Healthy Lifestyle (PHBS) in order to avoid helminthiasis.